SINTESIS KARBON AKTIF BERBASIS BIOMASSA SERAT BINTARO SEBAGAI BAHAN ELEKTRODA UNTUK APLIKASI SEL SUPERKAPASITOR - Aria Yunita; Rakhmawati Farma; Awitdrus Awitdrus; Irma Apriyani (Universitas Riau, 2023)
Biomass-based activated carbon has been widely developed due to its environmental friendliness, abundant availability, porous structure, high specific surface area and good electrical conductivity. One of the ways to improve the performance of supercapacitor cells is to increase the carbonization temperature, so that in this study various carbonization temperatures were carried out at 500°C, 600°C and 700°C. The results showed that the carbonization temperature of 600°C was the optimum temperature for making SB-based activated carbon. This is indicated by the results of measuring the physical properties of SB-600 in the form of the lowest density shrinkage value which can increase porosity thereby increasing the performance of supercapacitor cells. From this study, the highest capacitance value of 213 F.g-1 was found on the SB-600. The results obtained indicate that the selection of the optimum carbonization temperature is important and can improve the performance of supercapacitor cells.